Marine Environmental Management Strategies On The Activities Of Indonesia Archipelagic Sea Lane (ALKI) In The Lombok Strait Waters - Heru Kurniawan Alamsyah; Melda Kamil Ariadno; Arsegianto Arsegianto; Susi Watina Simanjuntak (Jurnal Perikanan dan Kelautan, 2022)
ABSTRACTThe acceptance of the concept of an archipelagic state in the 1982 United Nations Convention on the Law of the Sea (UNCLOS) brought logical consequences, especially in providing passage rights for foreign ships in international shipping. The Lombok Strait as one of the straits designated as Archipelagic Sea Lanes (ALKI) is the entry point for international shipping from the Indian Ocean to the Pacific Ocean, vulnerable to navigational threats and pollution of the marine environment. This study aims to analyze the current use of the Lombok Strait as the Indonesian Archipelagic Sea Lane (ALKI II) and analyze the priority strategies for managing the Lombok Strait. The method used in this research is descriptive analytical method and AHP (Analitycal Hierarchy Process) in determining the priority strategy of Lombok Strait management. The data collection technique was carried out by conducting observations, interviews and surveys using questionnaires as primary data and collecting documents, books and journals as secondary data sources. The results showed that the Lombok Strait management strategy showed that the main priority of Lombok Strait management was the ecological dimension. In terms of management strategy, the existence of good order at sea is an alternative to the main strategy for the ecological, economic, socio-cultural, legal and institutional dimensions.